1951
DOI: 10.1039/tf9514701360
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of methacrylic acid polymerization in aqueous solution

Abstract: The kinetics and reaction mechanism of the catalytic polymerization of methacrylic acid were investigated in aqueous solution. At pH 3-5-3-6, the overall reaction was found to be of first order with respect t o the monomer and t o vary as the square root of the catalyst concentration. From the decrease in reaction velocity with increasing pH (up t o pH 6, a t which the reaction velocity is practically zero), i t was concluded, that, t o a first approximation, only the non-ionized monomer takes part in the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 0 publications
3
30
0
1
Order By: Relevance
“…Until recently this was not reflected by the knowledge on polymerization kinetics of these monomers in aqueous phase. Early investigations [89][90][91] showed that variations in monomer concentration or pH may induce significant variations in the rate of polymerizations, but reliable rate coefficients were not available. Within the last decade, the PLP-SEC technique was also applied to polymerizations of water-soluble monomers.…”
Section: Polymerizations In Aqueous Phasementioning
confidence: 98%
“…Until recently this was not reflected by the knowledge on polymerization kinetics of these monomers in aqueous phase. Early investigations [89][90][91] showed that variations in monomer concentration or pH may induce significant variations in the rate of polymerizations, but reliable rate coefficients were not available. Within the last decade, the PLP-SEC technique was also applied to polymerizations of water-soluble monomers.…”
Section: Polymerizations In Aqueous Phasementioning
confidence: 98%
“…Equilibrium expressions for both the monomer ( 1 ) and polymer ( 2 ) are given by DNactual = 1-0.1 (This analysis assumes that an average K, value may be used for the polymer. Actually, this value depends on the chain length and chain conformation of the polymer such that a distribution of K, values corresponding to the distribution of polymer chain lengths and chain conformations better describes the actual system.)…”
Section: Theory Polymerization Of Carboxylic Acidsmentioning
confidence: 99%
“…Here an electrostatic potential barrier must be overcome, when a monomeric methacrylate anion approaches a terminal radical of a strongly charged poly-(methacrylic acid) chain. Low rate constants of propagation, as well as relatively high (as compared with acrylic acid) equilibrium monomer concentration allow us to explain the failure of the first attempts [112] to polymerize methacrylic acid in alkaline aqueous solution. Polymerization under these conditions is in fact possible, but its overall rate is lower by more than an order of magnitude than in acidic media, in which all species are protonated.…”
Section: )mentioning
confidence: 99%